(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
The current study was designed to evaluate the antioxidant effects of the chemical drug "Gemzar". In addition to study the role of the aqueous extract of the stigma of plant saffron to decrease the toxicity of Gemzar. In this study, 30 white adult rats aged 9-12 weeks were grouped into five groups (6 rats in each group ). The first group was negative control which received normal saline for four weeks. The second group was positive control received Gemzar in a dosage 15 mg/kg of body weight for four weeks. The third group was orally received a plant extract at a dosage of (100) mg/kg of body weight before medication for two weeks, then received drug for two weeks. The fourth group was received both plant extract (100) mg/kg and the drug for four weeks. The fifth group was received plant extract two weeks after medication. The experiment was maintained for four weeks, then the rats were killed, and the blood was drawn to study the pathological effects in the examined parameters. The statistical analysis showed a considerable decrease in catalase, albumin, with increasing of lipid peroxide levels in the group treated with drug in comparison with control group. However, the treatment with both plant extract 100 mg/kg and the drug was administered in three treatments with a plant extract (before, during, and after), the drug receiving. The current study showed a significant improvement in some cases of negative control. It may revealed that the exposure to Gemzar caused alterations in biochemical indicators of rats blood. The current study improved that that the uptake of the plant extract simultaneously with the drug or (before and after) the drug has a significant role to increasing the harm consequences caused by the drug.